2006
DOI: 10.1002/ange.200602879
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Superambrox: Stereoselective Type III Intramolecular Ene Reaction and OH‐Assisted Ru‐Catalyzed Isomerization

Abstract: Dedicated to Professor Georg Frµter on the occasion of his 65th birthdayIn the 1990s, chemists from Firmenich [1a] reported the isolation of (À)-1 by chemical degradation of the labdane diterpene (+)-larixol.[1b] This unsaturated analogue of Ambrox [2] was named "Superambrox" as a result of its excellent odor qualities (Scheme 1).To our knowledge, the only synthetic approaches towards Superambrox are based on acid-mediated polyene cyclizations, [3] which afford the racemate with low stereoselectivity in only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The catalyst displayed interesting TON for substrates having a mono‐ or disubstituted double bond, but was ineffective for allylic alcohols with higher substitution patterns (i.e., potential prochiral substrates). More recently, Fehr and Farris observed that Crabtree’s hydrogenation catalyst C (Figure 1) promoted an exclusive isomerization/lactolization sequence rather than the initially expected hydrogenation, even though a hydrogen atmosphere was maintained 8. 9 The observation by Baudry and Ephritikhine that C was also competent at promoting the isomerization of allylic alcohols, albeit with reproducibility issues, suggested the isomerization/lactolization sequence discovered by Fehr and Farris may be very substrate specific.…”
Section: Introductionmentioning
confidence: 98%
“…The catalyst displayed interesting TON for substrates having a mono‐ or disubstituted double bond, but was ineffective for allylic alcohols with higher substitution patterns (i.e., potential prochiral substrates). More recently, Fehr and Farris observed that Crabtree’s hydrogenation catalyst C (Figure 1) promoted an exclusive isomerization/lactolization sequence rather than the initially expected hydrogenation, even though a hydrogen atmosphere was maintained 8. 9 The observation by Baudry and Ephritikhine that C was also competent at promoting the isomerization of allylic alcohols, albeit with reproducibility issues, suggested the isomerization/lactolization sequence discovered by Fehr and Farris may be very substrate specific.…”
Section: Introductionmentioning
confidence: 98%
“…In the presence of a stoichiometric amount of EtAlCl 2 as the Lewis acid, only the ene-reaction occurs (Scheme 7). [36] The tricyclic ether 9 has notes of cedar, rotted wood and perspiration.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we described a stereoselective synthesis of rac ‐Superambrox ( 1 ) 1. The trans configuration of the tetrahydrofuran ring was obtained by an unprecedented, highly selective OH‐assisted Ir‐ or Ru‐catalyzed isomerization of diol 3 and subsequent reduction of lactol 4 by using Et 3 SiH2 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%